Analysis of Effective Factors on the way of spending of leisure time in Tehran (Case study: District 12 of Tehran) - Ali Movahed; Ali shamai; Mahnaz Bahmani (تحقیقات کاربردی علوم جغرافیایی)
Leisure is an integral part of everyday life in today's world. Today, leisure is a new social arena in which various factors influence. Understanding these factors and examining their role and their impact on active (external) and inactive (external) leisure has been a major part of proper city management since this day. Therefore, in this study, using exploratory method, we sought to identify the factors affecting leisure time in district 22 of Tehran. This is a cross-sectional, applied research. The method of data collection is survey and its tool is a questionnaire. This study, using inferential statistical methods and SPSS software and statistical analysis such as correlation, regression and t-test, attempted to analyze the relationship between independent research variables (functional, security, aesthetic, transportation, economic, biological). Environment and infrastructure facilities) and the dependent variable (active and inactive leisure time), to identify the maximum impact and the least impact of the variables. The results showed that the effect and correlation of factors on leisure time (active and inactive) were different. In other words, indoor or passive leisure time is less affected by the external environment and context. But on the other hand, leisure time active or foreign in the 22nd district of Tehran is strongly influenced by background conditions and the external environment. Aesthetic variables and infrastructure facilities have the highest relationship with active leisure time and economic, performance and economic components have the least impact. In the passive leisure time, most of the impact factor is related to infrastructure and least to economic component.